2018
DOI: 10.1111/bjd.17033
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of Staphylococcus aureus clonal complexes in atopic dermatitis: a follow‐up study

Abstract: The data indicate that temporal variation in S. aureus CC type is linked to flares of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Our results are in line with previous publications describing a heterogeneous population structure of S. aureus in AD and the absence of a prevailing strain [14, 21, 22]. Moreover, the most common spa -types found in our study population are also present in previously investigated AD populations and the general population, although the prevalence point estimates are not the same [14, 21-27]. This study confirmed that there are no specific spa -types preferentially colonizing patients with AD compared to healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with previous publications describing a heterogeneous population structure of S. aureus in AD and the absence of a prevailing strain [14, 21, 22]. Moreover, the most common spa -types found in our study population are also present in previously investigated AD populations and the general population, although the prevalence point estimates are not the same [14, 21-27]. This study confirmed that there are no specific spa -types preferentially colonizing patients with AD compared to healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…It was shown that the type of inflammation and immune signature characteristic of AD depends on the S. aureus strain [12]. Furthermore, it has been proposed that temporal variation in colonizing the S. aureus strain is an aggravating factor in AD due to a new trigger that is introduced to the immune system [13, 14]. This emphasizes that strain differences may contribute to the complexity of the disease, encouraging a more extensive investigation into the S. aureus populations in AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swabs are commonly used successfully to sample from eczematous skin surface of HE and AD. 12,19,40 Therefore, we used swabs, suitable for both skin and nasal collection of S. aureus, for comparison, and repeated sampling. 12,31,32 Our "real-life" study design is both a strength and a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The 'glove juice method' is ideal for bacteria sampling from hands, and particularly preferred in quantification of bacterial counts; however, this technique does not allow for comparison of lesional and non‐lesional skin, and the method is likely to influence subsequent samplings. Swabs are commonly used successfully to sample from eczematous skin surface of HE and AD 12,19,40 . Therefore, we used swabs, suitable for both skin and nasal collection of S. aureus , for comparison, and repeated sampling 12,31,32 …”
Section: Discussionmentioning
confidence: 99%